(untitled) (Journal of Management and Social Sciences, 2019)
While studies exist on international migration intentionalities in Africa, very few have sufficiently examined their kinship interfaces among the youths. Although, Africa remains a major migrant sending continent, the role of kinship in emigration is still poorly understood especially relative to the youths who are the most migratory. It is against this background that this article examined the intersectionalities of kinship and international migration in Nigeria with specific attention to youths’ ultimate actions informing intentions. The article adopted social action theory and the push and pull framework as its theoretical framework. The research design was descriptive and explorative. A total of 300 questionnaire was distributed through simple random sampling. 20 in-depth interviews were also conducted with purposively selected youths. The relationship between kinship and international migration intentionalities was found to be positive due to the previous and current kinship migration patterns, realities and expectations that have become normatively sanctioned within youths’ kinship networks. Hence, the kinship outcomes on migration co-relate with youths’ belief that Nigeria’s (like many other African countries’) social institutions are dysfunctional and infrastructural systems are opportunistically disabling for their values, goals and aspirations. Overall, the migration intentions and believed functionalities of emigrations among the youths are traceable to the subjective interpretations of migration values and outcomes within subsisting kinship systems usually predating and external to the youths.